CITRA DESTINASI, KUALITAS PELAYANAN DAN KEARIFAN LOKAL TERHADAP MINAT PENGUNJUNG - Lustono Lustono (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2020)
Tourism can be used as a leading sector in economic development, Banjarnegara has a unique and attractive natural wealth and potential namely the Dieng plateau. The existence of the Dieng plateau tourist attraction has encouraged the interest of tourists visiting both national and foreign tourists, the interest in annual visits has increased but not in accordance with the targets set by the Banjarnegara district. Improvements are still needed on the factors of fulfilling the needs and desires while traveling, and the comfort provided when traveling along with the improvement of the image of distination, quality of service and local wisdom in increasing visitor interest. This study aims to determine the effect of distortion image, service quality and local wisdom both partially and simultaneously on the interest of visiting tourists in Dieng, Banjarnegara Regency.The nature of this research is quantitative, with research variables are destination image, service quality, local wisdom and tourist visiting interests. The population in this study is the tourist attraction of Dieng Banjarnegara, the number of samples according to the Slovin formula is 97.6 rounded up by 100 respondents. The sampling technique uses accidental sampling. The data collection method uses a questionnaire. The analysis technique used is multiple linear regression with a significance level of 5%.The results of the destination image and service quality partially have a positive and significant effect on the interest of visiting tourists in Dieng, Banjarnegara Regency. Local wisdom partially has a positive and insignificant effect on the interest of visiting tourists in Dieng, Banjarnegara Regency. Destination image, service quality and local wisdom simultaneously influence the interest of visiting tourists. The interest of visiting tourists is influenced by destination image, service quality and local wisdom of 59.2%, there are still 40.8%, other factors not examined in this study